PROSES PEMBENTUKAN UNDANG-UNDANG PASCA PERGESERAN KEKUASAAN LEGISLATIF DARI PRESIDEN KE DPR - Kasim, Aminuddin (AKTUALITA, 2011)
Although there was a displecement of legislative power from president tohouse of respresentative after the amandement of indonesian constitution1945, the president still has major authority in proferring draft of law, themovement of president in discussing draft of law together with house ofrepresentative aimed at gaining common agreement (section 20, article (2)constitution of 1945, basically there is no different prior to the amandement ofindonesian institution 0f 1945. This mechanism shows that the displacement oflegislative power from president to house of representative (section 5, article(1) and section 20, article (1) of indonesian constitution of 1945) refers to thelinguistic shiffting not to the real meaning of displacement.Keyword: displecement of legislative power